2020
DOI: 10.1007/s12664-020-01069-0
|View full text |Cite
|
Sign up to set email alerts
|

A comprehensive review of vaccination in patients with inflammatory bowel diseases:  An Indian perspective

Abstract: The disease burden of inflammatory bowel diseases (IBD) in India is estimated to be one of the highest in the world in the near future. Patients with IBD, particularly those on immunosuppressive therapy, are at increased risk for developing vaccinepreventable illnesses. Adult vaccination policy and vaccination in patients with IBD are presently being at a very low level in India. This review discusses in detail the need for vaccination, levels of immunosuppression, a brief account of live and inactivated vacci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 77 publications
(87 reference statements)
0
5
0
Order By: Relevance
“…In contrast, patients with IBD did not suffer from an increased frequency of IBD flares after SARS-CoV-2 vaccination. Recent studies also proved the safety of other vaccines, such as the influenza vaccine, in patients with IBD [13,14]. A recent umbrella review of meta-analyses showed that vaccinations are not associated with an increased risk of IBD [15].…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, patients with IBD did not suffer from an increased frequency of IBD flares after SARS-CoV-2 vaccination. Recent studies also proved the safety of other vaccines, such as the influenza vaccine, in patients with IBD [13,14]. A recent umbrella review of meta-analyses showed that vaccinations are not associated with an increased risk of IBD [15].…”
Section: Discussionmentioning
confidence: 99%
“…The vaccination of individuals with IBD varies according to the recommendations of each country, as well as by the clinical judgment of the patient's healthcare provider[ 124 ]. It is recommended that these patients be vaccinated before starting immunosuppressive therapy, and if they have already started, vaccines with live viruses should be avoided[ 125 , 126 ]. Some authors recommend mandatory immunizations for these patients, including vaccines against influenza, chickenpox, hepatitis B, and triple viral.…”
Section: Clinical Management Of the Crohn’s Disease Today: How It Does?mentioning
confidence: 99%
“…If the test results are negative or show very low antibody levels, these patients should restart the vaccination schedule with three doses. Additionally, individuals over 50 years old should be immunized against the herpes zoster virus, and persons aged 9 to 45 years should be vaccinated for HPV, preferably covering the four main strains (6, 11, 16, and 18)[ 126 - 128 ]. The pneumococcal vaccine should be administered to all patients, following the recommendations of national immunization programs for chronic diseases[ 125 ].…”
Section: Clinical Management Of the Crohn’s Disease Today: How It Does?mentioning
confidence: 99%
See 1 more Smart Citation
“…It is well known that immunosuppression impairs the ability of the immune system to effectively respond to vaccination. Although recent reviews have examined the response to vaccination in patients who are immunosuppressed due to a particular disease state, 1 , 2 very few studies have examined the effect of immunosuppressive drug therapy on the response to inactivated vaccines. Though inactivated vaccines are generally considered safe in immunocompromised patients due to their inability to cause infection, questions regarding their efficacy, and whether all immunosuppressive drugs impact vaccine efficacy equally, remain.…”
Section: Introductionmentioning
confidence: 99%